Communication without identity: faces ofa latin america with own cultural marks - Aguirre Alvis, José Luis (2009)
In a global current social and cultural context in which the concept of diversity takes central place seems to be important to ask what it does mean to put in common or been in community or also to understand how the  idea of diversity introduces new dimensions to the concep t of social communication in irself. The proposal is ro build a renewederhic for rhe "al reri ty" which involves the competences for recognition, valorizarion  and respect ro rhe diversiry. A hope for a survival seems ro be linked ro rhe idea ofrhe renewal and recuperation of dialogue. The natural presence of a di verse human been in front of us is an existencial opporrunity ro be ourselves. The presence ofrhe "other" is related directly ro rhe ability of recognirion of our own exisrence. We need ro go fu rrher rhan rhe Descartes' idea of " I rhink rherefore I exist" for aho pefully pracrice of "1 communicare and rhen I can be" as a project of undersranding rhar rhe process of human communication implies necessarily the recognirion of a relation between narurally diverse actors. Diversiry is rhe central meaning and sense of a human process of communication